Film, mobility and urban space : a cinematic geography of Liverpool - Roberts, Les, 1966- (Liverpool University Press, 2012)
Drawing on multi-disciplinary debates surrounding the cultural production of place, space and memory in the post-industrial city, Film, Mobility and Urban Space explores the role of moving images in representations and perceptions of everyday urban landscapes. The arguments put forward in the book are based on a case study of Liverpool in the north west of England and draw from a unique spatial database of over 1700 archive films of the city from 1897 to the present day.